Joint Optimization of Network Lifetime and SNR in UAV-Assisted Edge Networks - Tripathi S.; Pandey O.J.; Hegde R.M. (My University, 2025)
One of the critical challenges of unmanned aerial vehicle (UAV)-assisted edge networks is to prolong the network lifetime with improved quality-of-service (QoS) at the sensor nodes (SNs). UAVs are typically resource-constrained with limited energy and communication capacity. Collaborative beamforming (CB) in a single antenna-mounted UAV network is an effective way of addressing the aforementioned challenges. Particularly, in this work, the optimal number of UAVs and their locations are obtained for CB, resulting in maximized network lifetime and improved signal-to-noise ratio (SNR). To meet the objective of maximizing network lifetime and SNR, antenna array gain is maximized by computing optimum spacing within the array. In this context, an optimization problem is formulated to jointly optimize the network lifetime and SNR. The proposed method minimizes the UAVs positioning error over time while forming the array. The method considers UAVs mobility parameters, the optimal number of collaborating UAVs, and UAVs power consumption as constraints. Finally, extensive simulation results show the effectiveness of the proposed method in terms of better network coverage, the minimum number of UAVs required, and maximum SNR compared to existing schemes. © 2022 IEEE.